2022
DOI: 10.3389/fcimb.2022.924707
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic and antifungal use in pediatric leukemia and lymphoma patients are associated with increasing opportunistic pathogens and decreasing bacteria responsible for activities that enhance colonic defense

Abstract: Due to decreased immunity, both antibiotics and antifungals are regularly used in pediatric hematologic-cancer patients as a means to prevent severe infections and febrile neutropenia. The general effect of antibiotics on the human gut microbiome is profound, yielding decreased diversity and changes in community structure. However, the specific effect on pediatric oncology patients is not well-studied. The effect of antifungal use is even less understood, having been studied only in mouse models. Because the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…In vaginal-delivered infants, Faecalibacterium levels were lower at the 1-year mark for babies that had received postnatal antibiotics at any point compared to babies that had not (Ainonen et al 2022 ). Another study reported that antibiotic and antifungal treatments diminished Faecalibacterium abundance in children with leukemia (Dunn et al 2022 ); the same result was seen in response to intraveinously administered antibiotics in individuals with multiple myeloma (D’Angelo et al 2022 ).…”
Section: Faecalibacterium As a Therapeutic Toolmentioning
confidence: 83%
“…In vaginal-delivered infants, Faecalibacterium levels were lower at the 1-year mark for babies that had received postnatal antibiotics at any point compared to babies that had not (Ainonen et al 2022 ). Another study reported that antibiotic and antifungal treatments diminished Faecalibacterium abundance in children with leukemia (Dunn et al 2022 ); the same result was seen in response to intraveinously administered antibiotics in individuals with multiple myeloma (D’Angelo et al 2022 ).…”
Section: Faecalibacterium As a Therapeutic Toolmentioning
confidence: 83%
“…For example, the chronological age of participants is a major determinant of gut microbiome maturation and could account for significant discrepancies in the relative abundance of different bacterial taxa between study groups 49 . Similarly, recent antibiotic exposure (depending on the class of the antibacterial agent, duration of exposure and its precise timing relative to specimen collection) can cause transient disturbances in the composition of the gut microbiome 69 , 74 , 79 and has the potential to obfuscate study group differences in the relative abundance of a subset of implicated taxa. However, given that antibiotic-induced dysbiosis and reduction in SCFA-producing taxa in mice and humans are usually reversible within a few weeks of exposure 64 , 65 , antibiotic exposure is unlikely to account for the consistent differences observed across all included studies.…”
Section: Gut Dysbiosis In Children With Allmentioning
confidence: 99%
“…One critical factor are medications, such as antibiotics, which can disrupt the balance of the gut microbiota, leading to dysbiosis that may affect cancer treatment outcomes. For example, although antibiotics are commonly administered in hematologic cancer treatment to prevent infections, they can affect bacteria such as Faecalibacterium, Anaerostipes, and Blautia, potentially disrupting the overall gut microbial ecosystem (Dunn et al, 2022;Sochacka-ćwikła et al, 2022).…”
Section: Other Factorsmentioning
confidence: 99%